2006
DOI: 10.1289/ehp.9322
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Arsenic Bioavailability in Rice and Its Significance for Human Health Risk Assessment

Abstract: BackgroundMillions of people worldwide consume arsenic-contaminated rice; however, little is known about the uptake and bioavailability of arsenic species after arsenic-contaminated rice ingestion.ObjectivesIn this study, we assessed arsenic speciation in greenhouse-grown and supermarket-bought rice, and determined arsenic bioavailability in cooked rice using an in vivo swine model.ResultsIn supermarket-bought rice, arsenic was present entirely in the inorganic form compared to greenhouse-grown rice (using irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 30 publications
8
158
2
Order By: Relevance
“…All experiential evidence to date suggests that arsenic bioavailability from rice grain is high, particularly for inorganic arsenic where swine studies suggest a gut bioavailability on the order of 90% (26). As rice bran solubles are themselves a soluble extract of bran, and are dissolved in water for their main formulated uses, this suggests that inorganic arsenic bioavailability from these products should also be high.…”
Section: Resultsmentioning
confidence: 99%
“…All experiential evidence to date suggests that arsenic bioavailability from rice grain is high, particularly for inorganic arsenic where swine studies suggest a gut bioavailability on the order of 90% (26). As rice bran solubles are themselves a soluble extract of bran, and are dissolved in water for their main formulated uses, this suggests that inorganic arsenic bioavailability from these products should also be high.…”
Section: Resultsmentioning
confidence: 99%
“…All indications are that the bioavailability of inorganic arsenic from rice is high, is in the order of 90% (Ackerman et al, 2005;Juhasz et al, 2006). Food standards are out of step with drinking water regulations which have received recent revision.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to gut bioavailability of inorganic arsenic in white rice, Juhasz et al (6) used large female white swine to compare orally gavaged or intravenously (IV) delivered pure arsenic salt solutions (arsenate, arsenite, MMA, and DMA) with white rice ingested as feed. They found that inorganic arsenic in rice had a high bioavailability at ∼90%.…”
Section: Table 3 Linear Regression Analysis Of Total Grain Arsenic Vmentioning
confidence: 99%